Muscle oxygen demands of the vastus lateralis in back and front squats - Davis, P. R.; Yakel, J. P.; Anderson, D. J. F. (International Journal of Exercise Science, 2020)
In resistance training squats are often used to strengthen the muscles of the lower extremities and core muscles. There are two common forms of squats that use a barbell for loading, the back squat and the front squat. The technique and loading of each squat differ markedly. However, the energetic demands on the muscle between the two forms are not well understood. The purpose of this study was to investigate the difference in energy demands between front and back squats by measuring the change in skeletal muscle oxygen saturation (SmO2) through the use of near infrared spectroscopy (NIRS). Methods: Eleven resistance trained individuals, (5 female, 6 male) with an average age of 23.7 ± 1.4, completed 3 sets of 15 repetitions at 70% of their 1-RM weight for both back and front squats. Skeletal muscle oxygen saturation (SmO2) of the vastus lateralis was measured using a wireless NIRS device. Results: The DeltamO2 was not significantly different between back and front squats but was different between sets 1-3 (44.76 ± 3.24% vs. 55.19 ± 2.75% vs. 56.30 ± 2.63%), main effect p = 0.0001 . The recovery of SmO2 was significantly different between back (42.5 ± 3.4 sec) and front squats (30.9 ± 2.8 sec), main effect p = 0.05. Conclusions: The findings of this study suggest that the energetic demands placed on the vastus lateralis during both front and back squats are similar with a slower recovery of energetics in the back squat.